Comparison of the quality attributes of carrot juice pasteurized by ohmic heating and conventional heat treatment - Negri Rodriguez, Livia Maria; Arias, Ricardo; Soteras, Trinidad; Sancho, Ana Maria; Tacca, Hernán; Aimaretti, Nora Rosa; Rojas Cervantes, María Luisa; Szerman, Natalia; Pesquero, Natalia; Rossetti, Luciana (2021)
This study aimed to evaluate the effect of pasteurization of carrot juice by heat treatment (80 °C – 7 min) and ohmic heating (OH) on its physicochemical and chromatic parameters, enzymatic and microbiological inactivation, volatile compounds, antioxidant capacity, carotene content, and sensory characteristics, compared to control juice (CJ). Both treatments allowed obtaining microbiologically stable and safe carrot juice and achieved 99% peroxidase inactivation levels. Significant differences were obtained in L* parameter, polyphenoloxidase activity and total antioxidant capacity, compared to HT-treated and CJ. The OH-treated juice presented greater color preference (p<0.05) by semi-trained panelists and a high level of acceptance among consumers (corresponding to "like extremely"). The results allow concluding that OH could be an alternative to conventional HT for the pasteurization of carrot juice, providing benefits in its sensory perception.